Respuesta :

INFORMATION:

We have the next subtraction

And we must solve it

STEP BY STEP EXPLANATION:

To solve a subtraction of two expressions, we must multiply the second expression by -1 and then add up the first expression and the result of the multiplication.

1. Multiply the second expression by -1

[tex]\begin{gathered} -1(3x+2y=3) \\ -3x-2y=-3 \end{gathered}[/tex]

2. Add up the first expression and the result of the multiplication. We must add similar terms

[tex]\begin{gathered} 3x+4y=17 \\ -3x-2y=-3 \\ -------- \\ 0x+2y=14 \\ →2y=14 \end{gathered}[/tex]

Finally, the result of the subtraction is 2y = 14

ANSWER:

aA. 2y = 14

Ver imagen BlueOtaku2056